High Oxygen Nanocomposite Barrier Films Based on Xylan and Nanocrystalline Cellulose - Saxena, Amit; Elder, Thomas J.; Kenvin, Jeffrey; Ragauskas, Arthur J. (Nano-Micro Letters, 2010)
The goal of this work is to produce nanocomposite film with low oxygen permeability by casting an aqueous solution containing xylan, sorbitol and nanocrystalline cellulose. The morphology of the resulting nanocomposite films was examined by scanning electron microscopy and atomic force microscopy which showed that control films containing xylan and sorbitol had a more open structure as compared to xylan-sorbitol films containing sulfonated nanocrystalline cellulose. The average pore diameter, bulk density, porosity and tortuosity factor measurements of control xylan films and nanocomposite xylan films were examined by mercury intrusion porosimetry techniques. Xylan films reinforced with nanocrystalline cellulose were denser and exhibited higher tortuosity factor than the control xylan films. Control xylan films had average pore diameter, bulk density, porosity and tortuosity factor of 0.1730 µm, 0.6165 g/ml, 53.0161% and 1.258, respectively as compared to xylan films reinforced with 50% nanocrystalline cellulose with average pore diameter of 0.0581 µm, bulk density of 1.1513 g/ml, porosity of 22.8906% and tortuosity factor of 2.005. Oxygen transmission rate tests demonstrated that films prepared with xylan, sorbitol and 5%, 10%, 25% and 50% sulfonated nanocrystalline cellulose exhibited a significantly reduced oxygen permeability of 1.1387, 1.0933, 0.8986 and 0.1799 cm3·µm/m2·d·kPa respectively with respect to films prepared solely from xylan and sorbitol with a oxygen permeability of 189.1665 cm3·µm/m2·d·kPa. These properties suggested these nanocomposite films have promising barrier properties.